Short-term outcomes of mirogabalin in patients with peripheral neuropathic pain: a retrospective study - Tetsunaga, Tomoko (J Orthop Surg Res, 2020)
BACKGROUND: Mirogabalin, which is approved for the treatment of peripheral neuropathic pain in Japan, is a ligand for the α2δ subunit of voltage-gated calcium channels. Both pregabalin and mirogabalin act as nonselective ligands at the α2δ-1 and α2δ-2 subunits. Mirogabalin has a unique binding profile and long duration of action. Pregabalin has been reported to produce intolerable adverse effects in some patients. This study investigated outcomes associated with mirogabalin administration in patients with peripheral neuropathic pain who ceased treatment with pregabalin. METHODS: We retrospectively assessed peripheral neuropathic pain using the neuropathic pain screening questionnaire (NeP score) in 187 patients (58 men, 129 women) who were treated with mirogabalin. All patients had switched from pregabalin to mirogabalin due to lack of efficacy or adverse events. Differences in the treatment course (i.e., numeric rating scale (NRS) scores) were compared using one-way analysis of variance with Bonferroni post hoc tests. RESULTS: The mean age of the patients was 72.3 years (range, 30–94 years), and the mean duration of disease was 37 months (range, 3–252 months). After treatment with mirogabalin for 1 week, NRS scores significantly decreased compared with baseline and continued to decrease over time. After 8 weeks, NRS scores improved by ≥ 30% from baseline in 113 patients (69.3%). Twenty-four patients (12.8%) stopped mirogabalin treatment due to adverse events. Somnolence (26.7%), dizziness (12.3%), edema (5.9%), and weight gain (0.5%) were noted as adverse events of mirogabalin. CONCLUSIONS: The results of this investigation indicate that mirogabalin is safe and effective for reducing peripheral neuropathic pain.